Setting the record straight some facts about the United Nations.
The United Nations is today, more than ever,engaged in service to all the world's nations and peoples,but its ability to function is hampered by financial problems.Unless Member States act quickly to pay their debts to the Organization -- a total of 2.3 billion dollar is owed as of mid-July 1997 -- the UN will remain in a precarious financial situation.It is clear that this situation stems in part from widespread public misunderstandings about what the UN really is -- and does.